Bangladesh's trade partners and the J-curve: an asymmetry analysis. Issue 2 (4th May 2019) - Bahmani-Oskooee, Mohsen; Rahman, Mir Obaidur; Abdul Kashem, Mohammad
ABSTRACT: Separating currency appreciations from depreciations and using non-linear models in recent literature have improved discovering significant link between the trade balance and the exchange rate. We add to this growing literature by considering the experience of Bangladesh with 11 trading partners. When a linear model was used, support for the J-curve effect was present only with one small partner. However, when a non-linear model was used, support increased to three countries including the largest partner, the United States, which accounts for more than 12% of Bangladesh's trade. Furthermore, the non-linear models supported short-run asymmetry adjustment as well as short-run asymmetry effects of exchange rate changes in most cases. However, long-run asymmetric effects were limited to a few.